(De)Automating the Future : Marxist Perspectives on Capitalism and Technology - Fehrle, Johannes,; Lieber, Marlon,; Ramírez, J. Jesse, (Historical Materialism Book Series ;, 2024)
Much has been written about the prospects of automation in recent years. While many have raised concerns over the threat of technological mass unemployment, others have anticipated a fully automated communist utopia which will provide material a